Absorption of electromagnetic radiation on human lower back region - Shakoor, M A; Moyeenuzzaman, M; Azim, R; Chakraborty, S R; M T Islam,; Samsuzzaman, M (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this paper a simulation study is conducted on lower back region of human phantom to observe the absorption of electromagnetic (EM) radiation. To investigate the effectiveness, EM radiation with different frequencies (1-100 GHz) is administrated step by step in different tissue thickness (up to 25 mm) of lower back region of human phantom and using EM simulator HFSS, return loss (RL) is recorded at every stage. From the results, it is found that when radiation with frequency 0.899 GHz to 1. 089 GHz (~1 GHz) is applied return loss is varies from 0.413 dB to 1.022 dB in different thicknesses. This indicates that only 1.1 % of the incident power is absorbed maximally. When radiation of 9.899 GHz to 10.099 GHz (~10 GHz) frequency is applied, the return loss value obtained is 6.731 dB to 6.280 dB for different tissue thicknesses. This indicates that only 10.1 % power is absorbed maximally. Finally, when radiation with frequency 99.899 GHz to 100.1 GHz (~ 0.1 THz) is applied, the return loss value is found ranging from 26.902 dB to 26.429 dB in different thicknesses which indicates that almost 99.9% of the incident radiation is absorbed by the human tissue i.e. almost 100% of the incident radiation is absorbed in human lower back region in THz range. From therapeutic point of view, almost the entire incident radiation is attenuated to the lower back region with THz radiation which is clinically very useful in treating chronic low back pain.